2021
DOI: 10.3389/fonc.2021.661012
|View full text |Cite
|
Sign up to set email alerts
|

Using Population-Based Cancer Registration Data and Period Analysis to Accurately Assess and Predict 5-Year Relative Survival for Lung Cancer Patients in Eastern China

Abstract: BackgroundThe assessment of long-term survival of lung cancer patients based on data from population-based caner registries, using period analysis, was scarce in China. We aimed to accurately assess the long-term survival of lung cancer patients, and to predict the long-term survival in the future, using cancer registry data from Taizhou City, eastern China.MethodsFour cancer registries with high-quality data were selected. Patients diagnosed with lung cancer during 2004–2018 were included. The long-term survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…For example, those who went to the hospital were more likely to have a stronger willingness to treatment and capacity to pay, and thus to receive better medical consultation and rehabilitation guidance, which emphasized the significance of active treatment. In addition, some studies reported higher survival in other regions (15,35,36), and the leading reason might be the decreases in the proportions of advanced lung cancer (stage III and stage IV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, those who went to the hospital were more likely to have a stronger willingness to treatment and capacity to pay, and thus to receive better medical consultation and rehabilitation guidance, which emphasized the significance of active treatment. In addition, some studies reported higher survival in other regions (15,35,36), and the leading reason might be the decreases in the proportions of advanced lung cancer (stage III and stage IV).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there have been several reports on the survival of lung cancer patients in Chinese population (12)(13)(14)(15)(16)(17) but they were mostly single-center studies with poor representativeness. A survival analysis based on 17 cancer registries in China with long-term follow-up (6) assessed the 5-year survival rates and the trends for all cancer types in recent years, but it lacked the specific survival in pathological stages and histological classifications.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of lung cancer was about 75% in the United States at the beginning of the 20th century [ 28 ]. Although it is estimated that the 5-year survival rate of NSCLC was increased from 40.2% in 2014–2018 to 52.7% in 2019–2023 in China [ 29 , 30 ], it is often diagnosed in advanced stages with a poor prognosis. Thus, there is an urgent need to elucidate the mechanism of lung cancer to identify potential therapeutic targets or prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations also suggested of improved survival for breast cancer patients due to early detection, early diagnosis and early treatment, as well as better socioeconomic status and diet ( 39 ) ( 40 ). Besides, Taizhou City is located in East China, with a relatively constantly prosperous economy, universal medical insurance system, and continuously improving health awareness, which may continue to contribute to future improvements of breast cancer survival in Taizhou City ( 7 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a global technical problem in assessing the long-term relative survival of cancer patients in a timely and accurate manner ( 8 ). The period analysis, first introduced in 1996 by Brenner and Gefeller ( 8 ), is the gold standard for the assessment of long-term survival of cancer patients from population-based cancer registry data and has been widely used globally ( 7 , 9 , 10 ). In addition, Brenner and his colleagues also proposed the model-based period analysis in 2006, which could provide a more precise survival prediction for the subsequent survival for cancer patients ( 11 ).…”
Section: Introductionmentioning
confidence: 99%